DEVELOPMENT OF CUSTOMER SERVICE INFORMATION SYSTEM IN SURYA SEMBADA PDAM SURABAYA - Dwi Aristyo Rahadiyan; Pantjawati Sudarmaningtyas; Sri Hariani Eko Wulandari (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2020)
PDAM Surya Sembada Surabaya city is a company distributing water in Surabaya. At present PDAM Surya Sembada in Surabaya has problems in serving customers in the activities of new installations and meter replacementsadueatoathealargevnumberxof requests for new installations and replacement of unserved meters. In 2018 there were 77,291 new installation requests and only 18% (13,912) of new installation requests underserved, and there were 51,649 requests for replace meters and only 21% (10,846) of request for meter replacements served by the PDAM because reports of requests that were on customer service were often not reported to the distribution. Reports on arrears of payment information from the finance department take 2 days so that the distribution department cannot find out information on delinquent payments quickly. This study aims to solve the problem by creating a customer service information system application that can make prospective customers and customers request new installations and replace meters through the application.aThe resultseof thehtrial on the function obtained 100% results based on these results thecapplication can be used to serve requests for new installations and replace meters and can provide information on customer water meter payment arrears.